A Comprehensive Review on Solid lipid Nanoparticles for precision targeting in chemotherapeutic delivery - Das, Abhra; Dutta, Pritam; Dutta, Isani; Bhakat, Sumit Prasad; Patra, Soumik; De, Himalay; Bhattacharyya, Soubhik; Majumdar, Shirsha; Koley, Soham (Journal of Neonatal Surgery, 2025)
To overcome the drawbacks of traditional drug delivery methods, solid lipid nanoparticles (SLNs) have become a ground breaking platform for the precise targeting of chemotherapeutic drugs. For hydrophobic medications, SLNs—which are made of biocompatible solid lipids—offer a special blend of stability, regulated release, and improved bioavailability. Improved cellular uptake and the possibility of tailored delivery by surface modifications with ligands that identify particular cancer cell markers are made possible by their nanoscale size. SLNs are very beneficial in the treatment of cancer because of their focused approach, which reduces systemic toxicity and increases therapeutic efficacy. The ability of SLN formulation approaches to deliver chemotherapeutics has been further enhanced by recent developments, such as the addition of multifunctional targeting moieties and the optimization of lipid composition. Furthermore, SLNs can be designed to offer prolonged release profiles, which would improve patient compliance and lower the frequency of administration. The promise of solid lipid nanoparticles as a flexible and successful precision medicine approach in oncology is highlighted in this abstract, opening the door to safer and more efficient cancer treatments.